Static flexural modes and piezoelectricity in 2D and layered crystals. Issue 12 (21st October 2016) - Michel, Karl H.; Neek‐Amal, Mehdi; Peeters, Francois M.
Abstract: Piezo‐ and flexoelectricity are manifestations of electromechanical coupling in solids with potential applications in nanoscale materials. Naumov et al. [Phys. Rev. Lett.102, 217601 (2009)] have shown by first principles calculations that a monolayer BN sheet becomes macroscopically polarized in‐plane when in a corrugated state. Here, we investigate the interplay of layer corrugation and in‐plane polarization by atomistic lattice dynamics. We treat the coupling between static flexural modes and in‐plane atomic ion displacements as an anharmonic effect, similar to the membrane effect that is at the origin of negative thermal expansion in layered crystals. We have derived analytical expressions for the corrugation‐induced static in‐plane strains and the optical displacements with the resulting polarization response functions. Beyond h‐BN, the theory applies to transition metal dichalcogenides and dioxides. Numerical calculations show that the effects are considerably stronger for 2D h‐BN than for 2 H − MoS 2 . Abstract : Piezo‐ and flexoelectricity are manifestations of electromechanical coupling in solids with potential applications in nanoscale materials. Michel et al. studied the in‐plane strain and electric polarization response of static corrugations in 2D crystals by anharmonic lattice dynamics. In contradistinction to previous continuum mechanics‐based work, the authors have found that contributions to the in‐plane electric polarization due to anomalous flexoelectric effects are less important than those due to out‐of‐plane strains. The magnitude of the polarization is larger in stiffer materials such as 2D h‐BN rather than in softer materials such as 2H‐MoS2 .